2023
DOI: 10.3389/fphar.2022.1079313
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of cognitive impairment using epigallocatechin-3-gallate in ovariectomized mice fed a high-fat diet involves remodeling with Prevotella and Bifidobacteriales

Abstract: Background: Estrogen deficiency and a high-fat diet (HFD) are both risk factors for Alzheimer’s disease (AD). HFD can accelerate cognitive impairment in estrogen-deficient patients, but there is currently no effective treatment. Epigallocatechin-3-galate (EGCG) is widely studied for its anti-inflammatory, anti-cancer, and anti-neurodegeneration effects. Nevertheless, whether EGCG can ameliorate cognitive impairment in HFD-fed estrogen-deficient mice has not been studied.Methods and Results: Ovariectomized (OVX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Mice with depression also had increased abundance of Actinobacteria ( 30 ). Ovariectomized (OVX) mice fed a high-fat diet experienced impaired object recognition and spatial memory associated with increased Bifidobacteriales ; administration of epigallocatechin gallate (EGCG) significantly improved cognition and memory and inhibited the increase of Bifidobacteriales ( 31 ). The results in our current study showed that IMB supplementation significantly improved cognition associated with significant reduction of Actinobacteria abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Mice with depression also had increased abundance of Actinobacteria ( 30 ). Ovariectomized (OVX) mice fed a high-fat diet experienced impaired object recognition and spatial memory associated with increased Bifidobacteriales ; administration of epigallocatechin gallate (EGCG) significantly improved cognition and memory and inhibited the increase of Bifidobacteriales ( 31 ). The results in our current study showed that IMB supplementation significantly improved cognition associated with significant reduction of Actinobacteria abundance.…”
Section: Discussionmentioning
confidence: 99%
“…In mice with estrogen deficiency and HFD-induced AD, EGCG administration (45 mg/kg bw) for 2 months improved object recognition and spatial memory, restored the diversity and structure of the gut microbiome in HFOVX mice, with increased Prevotella and inhibition of Bifidobacteriales but no effect on the decreases in Alloprevotella and Lactobacillaceae or on the increase in Enterorhabdus ( Fig. 6 ) [ 226 ]. Soto-Mercado et al [ 227 ] subsequently showed that EGCG treatment significantly inhibited the aggregation of (i)sAPPβf, blocked p-tau, increased ΔΨm, decreased oxidation of DJ-1 at residue Cys106-SH, and inhibited the activation of transcription factor c-JUN and P53, PUMA, and caspase-3 in mutant cholinergic-like neurons (ChLNs) compared to wild type.…”
Section: Dietary Small Molecules and Neuroprotection – A Overview Of ...mentioning
confidence: 99%